Exploring the impact of the SBAR on nursing handover: a scoping review - Soed, Nurfairy; Mohamed Ludin, Salizar; Syed Abdullah, Syed Nurulakla; Al-Zahrawi, Rasha (Asia Pacific Higher Learning Sdn. Bhd, 2025)
Effective communication during nursing handovers is vital for ensuring patient safety and continuity of care. The SBAR (Situation, Background, Assessment, Recommendation) communication tool offers a structured framework that enhances clarity, efficiency, and reliability during shift transitions. This scoping review assesses the impact of SBAR on nursing handovers, with a focus on its effectiveness in improving communication, reducing errors, and enhancing patient safety. The review methodology guided by the PRISMA-ScR checklist, a systematic literature search was conducted across Medline, CINAHL, EMBASE, and EBSCO databases for the period January 2021 to June 2024. Thematic analysis of the identified studies indicates that SBAR significantly improves communication quality and patient safety, reduces handover-related errors, and promotes teamwork among nursing staff. Three studies reported notable reductions in errors, while two studies documented increased satisfaction among nurses and patients. Additionally, SBAR was associated with educational benefits, including improved knowledge and confidence in the handover process. The structured nature of SBAR contributes to a decrease in sentinel events linked to miscommunication and enhances nurses' confidence and satisfaction with the handover process, thereby supporting teamwork and overall quality of care. Despite these positive outcomes, challenges remain in its implementation and integration across diverse healthcare settings. Further research is warranted to examine the long-term benefits of SBAR, compare its effectiveness with other communication tools, and optimize its application in varied clinical contexts. Addressing these areas will support SBAR's continued role in improving nurse performance, patient safety, and healthcare quality.